Estimation of exciton reverse transfer for variable spectra and high efficiency in interlayer-based organic light-emitting devices. (3rd November 2016) - Liu, Shengqiang; Zhao, Juan; Huang, Jiang; Yu, Junsheng
Abstract: Organic light-emitting devices (OLEDs) with three different exciton adjusting interlayers (EALs), which are inserted between two complementary blue and yellow emitting layers, are fabricated to demonstrate the relationship between the EAL and device performance. The results show that the variations of type and thickness of EAL have different adjusting capability and distribution control on excitons. However, we also find that the reverse Dexter transfer of triplet exciton from the light-emitting layer to the EAL is an energy loss path, which detrimentally affects electroluminescent (EL) spectral performance and device efficiency in different EAL-based devices. Based on exciton distribution and integration, an estimation of exciton reverse transfer is developed through a triplet energy level barrier to simulate the exciton behavior. Meanwhile, the estimation results also demonstrate the relationship between the EAL and device efficiency by a parameter of exciton reverse transfer probability. The estimation of exciton reverse transfer discloses a crucial role of the EALs in the interlayer-based OLEDs to achieve variable EL spectra and high efficiency.